Синтез систем управления генетическими алгоритмами на основе интегральных квадратичных оценок - Никулина, Елена Николаевна; Северин, Валерий Петрович; Бондаренко, Анатолий Васильевич (НТУ "ХПИ", 2013)
The problem of synthesis of automatic control systems on the base of improved integral square estimates of quality is considered. Genetic algorithms using local optimization methods are developed. Integral estimates for test systems are minimized.
Keywords: системы автоматического управления; оценка качества; оптимизация локальная; системы тестовые